Behavior of Nutritional Supplements Use in Association With Inflammatory Skin Diseases in Chinese College Students - Yuan, Yan; Su, Juan; Li, Ji; Tao, Juan; Kang, Xiaojing; Wu, Bin; Shan, Shijun; Wang, Xiaohui; Chen, Xiang; Shen, Minxue; Jiang, Liyuan (Frontiers in Nutrition, 2021)
Objectives: It is understudied how frequently adolescents use nutritional supplements (NS) and whether the corresponding behavior is associated with skin diseases that may cause unpleasant symptoms and disfigurement. The current study aimed to investigate the prevalence of NS use in Chinese college students and its association with inflammatory skin diseases. Methods: This was a university-based epidemiologic investigation that included 20,138 students who underwent dermatological examinations. A questionnaire survey was conducted to inquire about the use of NS along with related information. Skin diseases were diagnosed by dermatologists during the health examination. Logistic regression models were used for analysis. Adjusted odds ratios (aORs) were presented as the effect size. Results: Survey responses from a total of 20,138 participants were analyzed. Specifically, 18.3% of the participants reported the use of NS in the past year. The use of vitamin C was most frequently reported, accounting for a proportion of 12.9%, followed by vitamin B and mineral supplements. The use of NS was found to be associated with female sex, Han ethnicity, higher annual household income, and a series of healthy lifestyles such as more physical activity, less second-hand smoke exposure, less alcohol consumption, and higher intake of milk and yogurt (p < 0.001). Participants with chronic urticaria (aOR = 1.3; 95% CI, 1.0–1.7), atopic dermatitis (aOR = 1.4; 95% CI, 1.2–1.6), or acne (aOR = 1.17; 95% CI, 1.04–1.31) were more likely to use NS, especially herbs (aOR = 2.7; 95% CI, 1.2–3.7), followed by vitamin B (aOR = 1.6; 95% CI, 1.2–2.0) and mineral supplements (aOR = 1.4; 95% CI, 1.0–2.0). Conclusion: College students with inflammatory skin diseases are more likely to use NS.